2021
DOI: 10.1111/cid.12993
|View full text |Cite
|
Sign up to set email alerts
|

The influence of insertion torque values on the failure and complication rates of dental implants: A systematic review and meta‐analysis

Abstract: Background The influence of using different insertion torque values on clinical and radiographic outcomes of implant therapy is unclear in the current literature. The aim of this systematic review and meta‐analysis was to evaluate the implant outcomes and complications rates using high insertion torque values compared with those using regular insertion torque value levels. Methods Randomized controlled trials (RCTs), nonrandomized controlled clinical trials (NRCCTs), prospective and retrospective cohorts were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 58 publications
1
14
0
Order By: Relevance
“…They also pointed out that, at implant sites where the cortical bone was more represented (mandible), the use of high IT produced the worst clinical effects. However, recent systematic reviews on this subject underline that studies concerning the association between high IT and marginal bone loss are still inconclusive, and more research is recommended on the matter [ 46 , 47 , 48 ].…”
Section: Measurements For Stability Of Dental Implantsmentioning
confidence: 99%
“…They also pointed out that, at implant sites where the cortical bone was more represented (mandible), the use of high IT produced the worst clinical effects. However, recent systematic reviews on this subject underline that studies concerning the association between high IT and marginal bone loss are still inconclusive, and more research is recommended on the matter [ 46 , 47 , 48 ].…”
Section: Measurements For Stability Of Dental Implantsmentioning
confidence: 99%
“…24 However, when comparing high torque with regular torque values in respect to failure and complication rates, a systematic review with meta-analysis showed no significant difference in these short-term outcomes, at least concerning standard diameter implants. 25 The results of this study show that final insertion torque varies significantly depending on patients' clinical anatomy and the technical procedures employed during surgery. Concerning the drilling protocol, bone types I and II required full length preparation with the needle drill for achieving optimal torque, whereas in cases with low density bone, undersized drilling was required for reaching sufficient insertion torque.…”
Section: Discussionmentioning
confidence: 82%
“…Insertion torque has been shown to affect the outcome of mini implant treatment, with low torque being correlated with severe marginal bone loss cases 24 . However, when comparing high torque with regular torque values in respect to failure and complication rates, a systematic review with meta‐analysis showed no significant difference in these short‐term outcomes, at least concerning standard diameter implants 25 …”
Section: Discussionmentioning
confidence: 99%
“…In our study, of the 50 implants that failed, 27 failed shortly (3.92%) and 23 failed long (3.34%) after the procedure, corroborating previous findings. 22 In this study, we grouped the provisional (14, acrylic resin crown) and metal-ceramic (9) prostheses in late failures since the masticatory loads are distributed in similar ways in both materials. 32 This study has several limitations due to its retrospective nature.…”
Section: Discussionmentioning
confidence: 99%